MODEL KOOPERATIF TIPE PREVIEW QUESTION READ REFLECT RECITE REVIEW TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DI SD - Tikawara, Anggela; Utami, Sri; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine mastery of the effect of the application of Type preview question read reflect recite review variation on math learning on learning outcomes of the fourth grade students of SDN 16 Pontianak South?